Efficient wide-bandgap copolymer donors with reduced synthesis cost. Issue 45 (28th June 2021) - Xu, Jingui; Sun, Anxin; Xiao, Zuo; Wang, Ergang; Zhang, Bin; Hua, Yong; Ding, Liming
Abstract : Two wide-bandgap copolymer donors with reduced synthesis cost offered decent PCEs up to 15.25% in organic solar cells. Abstract : Two wide-bandgap copolymer donors, W4 and W5, based on mono-fluorine- and mono-alkoxyl-substituted benzene units were developed. W4 and W5 were synthesized from cheap and commercially available starting materials. Organic solar cells based on W4 and W5 gave decent power conversion efficiencies of up to 15.25%.